Serious Games for Healthy Nutrition. A Systematic Literature Review - Ifeoma Adaji (Serious Games Society, 2022)
Research indicates that the two main causes of being overweight and obese are living a sedentary lifestyle and unhealthy eating habits. Influencing people to be active and exercise is an active research area that has resulted in the development of several games both commercially available and for free. The area of influencing people to develop healthy eating habits, on the other hand, still has room for growth. In the current paper, I review existing serious games for healthy nutrition over the past five years and summarize the main findings based on three main themes: the design and development of the game, the evaluation of the game, and the findings from the evaluation. My results indicate that most games are designed in collaboration with a team of experts such as nutritionists, psychologists, HCI designers, and software developers. In addition, most of the games for kids are web-based while most of those for adults are mobile-based. Most games used a self-report approach to evaluation which was carried out over a range of period of 30 minutes to 90 days with between 10 to 531 participants. There were mixed results from the evaluations with most games partially achieving their aim. I conclude by suggesting guidelines for developing serious games for influencing healthy nutrition.